Serengeti III : human impacts on ecosystem dynamics - Sinclair, A. R. E. (Anthony Ronald Entrican) (University of Chicago Press, 2008)
Serengeti National Park is one of the world?s most diverse ecosystems, a natural laboratory for ecology, evolution, and conservation, with a history that dates back at least four million years to the beginnings of human evolution. The third book of a ground- breaking series, Serengeti III is the result of a long-term integrated research project that documents changes to this unique ecosystem every ten years. Bringing together researchers from a wide range of disciplines?ecologists, paleontologists, economists, social scientists, mathematicians, and disease specialists? this volume focuses on t.